2020
DOI: 10.7759/cureus.7991
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Cause of Bilateral Corneal Ulcers: Vitamin A Deficiency in the Setting of Chronic Alcoholism

Abstract: Vitamin A deficiency is rarely encountered in the western world. When encountered, vitamin A deficiency is seen as a component of the malabsorption spectrum of disease. Given the infrequency of nutritional deficits in the developed world, vitamin A-associated ophthalmologic disease is rarely encountered. We report a case of a 56-year-old male with severe vitamin A deficiency in the setting of alcoholic liver cirrhosis. This case emphasizes two important points. First, it considers vitamin A deficiency as a cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…12 Chronic liver disease can be associated with a severe form of VAD because of 3 mechanisms: low dietary intake, malabsorption, and loss of hepatocytes. 13 Alcohol-associated cirrhosis may be more commonly associated with VAD than other etiologies such as viralassociated cirrhosis because of poor dietary intake and malabsorption. 14,15 Sohal et al 13 previously reported a patient with corneal ulcers secondary to alcohol-associated cirrhosis-induced VAD; however, they were unable to track corneal ulcer progression in response to vitamin A supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Chronic liver disease can be associated with a severe form of VAD because of 3 mechanisms: low dietary intake, malabsorption, and loss of hepatocytes. 13 Alcohol-associated cirrhosis may be more commonly associated with VAD than other etiologies such as viralassociated cirrhosis because of poor dietary intake and malabsorption. 14,15 Sohal et al 13 previously reported a patient with corneal ulcers secondary to alcohol-associated cirrhosis-induced VAD; however, they were unable to track corneal ulcer progression in response to vitamin A supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…13 Alcohol-associated cirrhosis may be more commonly associated with VAD than other etiologies such as viralassociated cirrhosis because of poor dietary intake and malabsorption. 14,15 Sohal et al 13 previously reported a patient with corneal ulcers secondary to alcohol-associated cirrhosis-induced VAD; however, they were unable to track corneal ulcer progression in response to vitamin A supplementation. Patients with advanced fibrosis and cirrhosis may experience a significant decrease in the number of hepatocytes responsible for the primary storage of vitamin A, leading to possible acute/ subacute VAD.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic alcohol intake results in decreased oral retinoid intake while also increasing retinol breakdown by inducing enzyme activity [ 12 ]. In patients with cirrhosis, decreased oral intake of vitamin A along with decreased intestinal absorption of vitamin A results in vitamin deficiency that can cause ocular symptoms [ 13 ]. Bitot spots are one such manifestation, presenting as keratinous accumulations on the cornea usually preceded by ocular xerosis and ultimately leading to keratoconjunctivitis.…”
Section: Introductionmentioning
confidence: 99%
“…Bitot spots are one such manifestation, presenting as keratinous accumulations on the cornea usually preceded by ocular xerosis and ultimately leading to keratoconjunctivitis. If extensive, a vitamin A deficiency in cirrhotic patients can even lead to corneal necrosis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%